Uma prática didático-pedagógica de educação financeira no 6º ano do ensino fundamental - DOMINGOS, Nayara da Silva (2022)
This research addresses Financial Education as a relevant topic that needs to be further discussed from an academic perspective, as people's financial education can contribute to the planning of the family budget and the development of the country's